Systematic Literature Review: Pengaruh live streaming commerce, gamification experience, personalization recommendation dimediasi oleh customer engagement terhadap purchase Decision Pada Marketplace - nurmalasari, Nurmalasari (Jurnal Ekonomi STIEP, 2024)
This systematic literature review tries to answer the question of what research results and methods are used by searching for several variables The effect of live streaming commerce, gamification experience, personalized recommendations mediated by customer engagement on purchase decisions. This research uses a qualitative method with a literature study approach is a Systematic Literature Review (SLR) with the prism method with the help of Watase Uake, and the Mendeley Application. This research is limited by only looking for Scopus Q1, Q2, Q3, and Q4 journal articles, published in 2023-2024. Based on 408 articles reviewed, through a systematic literature review process, with article publication time in 2024. The results showed that 13 articles met the criteria and were used as references in this study. The results showed that in the context of e-commerce and live streaming, various factors such as information quality, social interaction, influencer characteristics, and emotional elements play an important role in influencing consumer behavior. Platform quality and parasocial relationships can increase perceived value and user engagement, while content credibility and streamer authenticity contribute to purchase decisions, suggesting that effective marketing strategies and a deep understanding of consumer interactions are critical to driving impulse purchase behavior and improving the overall consumer experience.